Konsep Tuhan, Manusia, dan Alam Dalam Tradisi Begawi Cakak Pepadun Lampung: Sebuah Kajian Metafisika - Shely Cathrin (Jurusan Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2021)
This study aims to analyze the concepts of God, nature, and humans in the Begawi Cakak Pepadun Lampung tradition from a metaphysical point of view. An investigation of these three concepts is an urgent thing to do to formulate the elements of Nusantara philosophy contained in the Begawi Cakak Pepadun Lampung tradition, as well as to trace the influence of Islam in the implementation of the tradition. Researchers conducted an analysis of the Begawi Cakak Pepadun Lampung tradition from a metaphysical point of view with a research model on philosophical issues that exist in society. The results showed that the concept of God, in the Begawi Cakak Pepadun tradition, was influenced by Islam. God is understood as the Supreme Being, Supreme One, and the highest Source of Law. Humans attain perfection of themselves as humans when they fulfill three stages of life, namely cakak pelaminan, cakak haji, and cakak pepadun. This is the concept of a perfect human being implied in the Begawi Cakak Pepadun tradition. The universe is understood as consisting of the material and spiritual realms as a creation that shows the majesty of God. This concept is influenced by the teachings of Islam about a balanced relationship between humans and God (hablu minallah), and humans and humans (hablu minannas).